PRO-KONTRA PEMEKARAN PAPUA: SEBUAH PELAJARAN BAGI PEMERINTAH PUSAT - Romli, Lili (Pusat Penelitian Politik, 2006)
The division ofthe Province of Papua is an interesting case in pos t reform era in which local government autonomy is a hot topic in local politics in Indonesia. The decision to divide the province comes from Central Government in Jakarta, not provincial government in Jayapura. The decision raises dispute argument in pro or contra on the necessary of the division between people of Papua. The paper aims is to describe the discord between the problem of the Division ofPapua in the level offormal rule and the pro and contra to the decision. To solve the problem ofpro and contra, this paper argues that it is necessary to give more room for people ofPapua to decide what it need. By involving local institution that has been legally approved as representatives of Papuan people, such as Papuan People Assembly (Majelis Rakyat Papua, MRP) and DPRD, the pro and contra to the division among people and government will be solved in dialogic decision.